IDENTIFIKASI DIVERSITAS MAKROFAUNA TANAH DI AREA TAMBANG PANAS BUMI MUTUBUSA DESA SOKORIA KECAMATAN NDONA TIMUR - Fatria Ika Ndati Rhengi; Agustinus J P Ana Saga; Philipus N. Supardi (AGRICA, 2022)
Soil macrofauna is animals that have a body size of 2-20 mm. The main place of life for macrofauna is not only above but also underground. The purpose of this study was to determine the diversity of soil macrofauna and environmental conditions on forest land and agricultural land in the Mutubusa Geothermal Mine area. The selection of research sites using the purposive sampling method and The sampling technique was carried out by the monolith sampling method. Observational variables in this study were diversity index, relative frequency, density index, and relative density. The results of the diversity analysis show that there are ten types of soil macrofauna, that is; Cockroaches, Millipedes, Spiders, Ants, Conch, Earthworms, Crickets, Grasshoppers (H' = 1.67), Mixed Fields (H' = 1.32), and Coffee Fields (H' = 1.28). While the density of soil macrofauna in candlenut land is 2.9%, forest land is 0.2%, mixed land is 1.5% and coffee land is 0.4%. The highest important value index in candlenut land was snail species, amounting to 39%, while in forest and mixed land, the highest important value index was ant species, respectively, 41% and 67%.